Apakah Belanja Daerah Mampu Memoderasi Pengaruh Kondisi Sosial Dan Ekonomi Masyarakat Terhadap Kepatuhan Pajak Di Daerah Provinsi? - Kuncoro Aji, Anggit (Universitas Katolik Soegijapranata, Semarang, 2025)
This study aims to examine the impact of social and economic conditions on tax compliance across various provinces in Indonesia, with regional expenditure as a moderating variable. The research covers all 34 provinces, utilizing data from 2014 to 2022. Economic conditions are measured using provincial GDP growth and the Gini ratio, while social conditions are represented by the Human Development Index (HDI) and the poverty rate in each province. The moderating variable, regional expenditure, is measured using the total realized expenditure of each province. Attribution theory, fairness heuristic theory, slippery slope theory, stakeholder theory, and the fiscal synchronization hypothesis are applied to analyze the relationships between variables. This study employs a quantitative approach using secondary data and applies descriptive statistics and multiple linear regression analysis. The results indicate that HDI consistently has a positive effect on tax compliance. Regional expenditure effectively moderates the relationships between variables. However, other variables such as the poverty rate, GDP growth, and the Gini ratio do not significantly impact tax compliance. Therefore, provincial governments should focus on improving the quality of life for their citizens and enhancing the effectiveness of regional expenditures to increase tax compliance.